Perlindungan Hukum Terhadap Pemutusan Hubungan Kerja Sepihak Bagi Pekerja - Naibaho, Jansen Hasiholan; Rizki, Rizal Maulana; Fernanda, Cerli Maulana; Reza, Muhammad Rifqi; Pandapotan, Fransisko (Journal of Industrial Relations Studies, 2025)
Unilateral termination of employment (PHK) remains a serious issue in the practice of industrial relations in Indonesia. One case that reflects this issue occurred at Company X, where six workers were dismissed without following lawful procedures. This study aims to analyze the legal protection for workers in cases of unilateral termination of employment based on Law Number 13 of 2003 concerning Manpower and to identify violations of workers' normative rights. The research method used is a normative juridical approach with literature study techniques and secondary data from labor institution documents. The results of the study indicate that Company X violated the provisions of Article 151 and Article 156, such as failing to conduct bipartite negotiations and not providing compensation. The conclusion affirms that although legal protection is normatively regulated, its implementation in practice remains suboptimal, thus requiring strengthened supervision and law enforcement